The use of touch DNA analysis in forensic identification focusing on Short Tandem Repeat-Combined DNA Index System loci THO1, CSF1PO and TPOX - Ahmad Yudianto; Indah Nuraini M.; Abdul Hadi Furqoni; Simon Martin Manyanza Nzilibili; Pudji Harjanto (MDPI AG, 2020)
Forensic identification through DNA analysis is an accurate diagnostic tool. Deoxyribonucleic Acid (DNA) analysis is via DNA repetitive regions with less than 1 kb base size is called 'microsatellite' or Short Tandem Repeat (STR). At the crime scene, the perpetrator's skin may accidentally be in contact with surrounding objects, thereby transferring trace evidence to the objects. In this study DNA was obtained using "touch DNA" from two buccal smears and two smear from watches and cellphones from volunteers who had signed the consent form. Samples were isolated using DNAzol. The quantity of DNA obtained will be measured using a UV spectrophotometer. For DNA amplification using 3 STR CODIS loci namely TH01, CSF1PO, and TPOX. The last step is visualization using acrylamide gel and silver staining. Mean levels of DNA (UVVisible Spectrophotometer) were 167.89±85.71 μg/mL for the buccal swab, 59.19±5.58 μg/mL for the watch swab, and 38.09±2.12 μg/mL for the mobile swab; the purity of the buccal swab DNA was 1.79±0.71, of the watch swab 1.69±0.76, and of the mobile swab 1.53±0.56. Visualization of PCR products on Polyacrylamide Agarose Composite Gel Electrophoresis stained with Silver and amplified using the standard primers THOI, TPOX and CSF1PO for STR Combined DNA Index System (CODIS) showed a 100% detection of amplicons. Both the buccal swab, watch swab and handphone swabs had trace amount of DNA that was sufficient to be isolated and amplified by using Polymerase Chain Reaction on the STR CODIS loci THO1, CSF1PO and TPOX.